ANALISIS PENOLAKAN PENDIRIAN PT JAKA MITRA MENURUT PERATURAN DAERAH LAMONGAN (PERDA) NOMOR 01 TAHUN 2014 TENTANG IZIN LINGKUNGAN: Studi Kasus Pendirian PT Jaka Mitra di Desa Kemantren Kecamatan Paciran Lamongan Jawa Timur - Moch. Haidar Ali Al-Hamid (The Republic : Journal of Constitutional Law, 2023)
The purpose of this research is to find out the community's rejection of the Paciran Lamongan Kemantren Village community for the development of PT Jaka Mitra which is constrained by the AMDAL problem which is seen from the normative point of view of the Lamongan Regency Regional Regulation Number 1 of 2014 concerning Environmental Permits. The research method used in this research is normative research, emphasizing the function of AMDAL as an instrument to prevent pollution and environmental damage. in normative research, the processing of legal materials is systematized by law. Legal materials are then analyzed qualitatively, analyzing with systematic thinking to provide answers to problems. The results of this study are that AMDAL as one of the requirements in environmental permits is a study of activities that are systematically and scientifically regulated using an interdisciplinary and even multidisciplinary approach, therefore AMDAL research must be structured in a coherent and comprehensive-integral manner. When this is not resolved, the development of industrial estates cannot be carried out, this is as an example of the case that happened to PT Jaka Mitra which resulted in the revocation of permits and termination of the project due to EIA problems. Keywords: Research, Regulation, Analyzing, interdisciplinary, development